The effect of emotional intelligence and motivation on turnover intention through burnout in management trainee program employees (a study on Wom Finance) - Muhammad Bastaruddin; Hery Winoto (Jurnal Mantik, 2026)
This study aims to analyze the influence of emotional intelligence and motivation on turnover intention through burnout in employees in the management trainee program (a study at WOM Finance). The Management Trainee program runs for three years from the time the employee joins the company. Data on employees in the active Management Trainee program recorded as of December 31, 2025, showed that the company had 467 Management Trainee program participants. The sample size was 82 respondents who met the minimum requirements for PLS analysis. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS 4 application. The results of the first hypothesis test indicate that emotional intelligence influences turnover intention. This finding is supported by the t-test results, which showed a calculated t-value of 2.117 and a probability value of 0.007 (<0.05), of the second hypothesis test indicate that work motivation influences turnover. This finding is supported by the t-test results, which showed a calculated t-value of 2.818 and a probability value of 0.014 (<0.05), of the third hypothesis test indicate that emotional intelligence influences burnout. This finding is supported by the t-test results, which showed a calculated t-value of 2.832 and a probability value of 0.006 (<0.05), of the fourth hypothesis test indicate that work motivation influences burnout. This finding is supported by the t-test results, which showed a calculated t-value of 6.281 and a probability value of 0.000 (<0.05), of the fifth hypothesis test indicate that burnout influences turnover. This finding is supported by the t-test results, which showed a calculated t-value of 2.691 and a probability value of 0.040 (<0.05), of the sixth hypothesis test indicate that burnout mediates the effect of emotional intelligence on turnover intention. This finding is supported by the t-test results, which showed a calculated t-value of 2.379 and a probability value of 0.005 (<0.05), of the seventh hypothesis test indicate that burnout mediates the effect of work motivation on turnover. This finding is supported by the results of the t-test which shows a t-count value of 2.658 and a probability value of 0.011 (<0.05).